Simultaneous Pi2 observations by the Van Allen Probes inside and outside the plasmasphere. Issue 6 (11th June 2015) - Ghamry, E.; Kim, K.‐H.; Kwon, H.‐J.; Lee, D.‐H.; Park, J.‐S.; Choi, J.; Hyun, K.; Kurth, W. S.; Kletzing, C.; Wygant, J. R.; Huang, J.
Abstract Plasmaspheric virtual resonance (PVR) model has been proposed as one of source mechanisms for low‐latitude Pi2 pulsations. Since PVR‐associated Pi2 pulsations are not localized inside the plasmasphere, simultaneous multipoint observations inside and outside the plasmasphere require to test the PVR model. Until now, however, there are few studies using simultaneous multisatellite observations inside and outside the plasmasphere for understanding the radial structure of Pi2 pulsation. In this study, we focus on the Pi2 event observed at low‐latitude Bohyun (BOH, L = 1.35) ground station in South Korea in the postmidnight sector (magnetic local time (MLT) = 3.0) for the interval from 1730 to 1900 UT on 12 March 2013. By using electron density derived from the frequency of the upper hybrid waves detected at Van Allen Probe‐A (VAP‐A) and Van Allen Probe‐B (VAP‐B), the plasmapause is identified. At the time of the Pi2 event, VAP‐A was outside the plasmasphere near midnight (00:55 MLT and L =∼ 6), while VAP‐B was inside the plasmasphere in the postmidnight sector (02:15 MLT and L =∼ 5). VAP‐B observed oscillations in the compressional magnetic field component (Bz) and the dawn‐to‐dusk electric field component (Ey), having high coherence with the BOH Pi2 pulsation in the H component. The H‐Bz and H‐Ey cross phases at VAP‐B inside the plasmasphere were near −180° and −90°, respectively. These phase relationships among Bz, Ey, and H are consistent with a radially standing oscillation of the fundamental mode reported in previous studies. At VAP‐A outside the plasmasphere, Bz oscillations were highly correlated with BOH Pi2 pulsations with ∼−180° phase delay, and the H‐Ey cross phase is near −90°. From these two‐satellite observations, we suggest that the fundamental PVR mode is directly detected by VAP‐A and VAP‐B.